Analisis Kinerja Keuangan Perusahaan Eastparc Hotel Menggunakan Rasio Keuangan - Putri, Tasya Tania; Darul Fadli, Uus Mohammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to assess the financial statements of Eastparc Hotel by using financial ratios to determine its performance. The methodology used in this article is quantitative descriptive analysis method, which seeks to explain the research findings by presenting financial statement data relating to the company's performance. This research has identified specific issues to be investigated about the financial performance of the Eastparc Hotel company, specifically focusing on the company's financial statement data. on 31 December 2021 to 31 March 2022. Based on the results of the research analysis obtained, PT Eastparc Hotel Tbk showed improvements in several aspects of profitability, especially in terms of operational efficiency and financial management. However, the decline in gross profit margin needs to be examined and analysed further to ensure the right strategy in managing costs and revenues. Nonetheless, improvements in net profit margin, ROI, and ROE indicate better financial performance and effectiveness in using resources and equity. In addition, the company successfully reduced reliance on debt, increased the use of equity capital, and delivered better returns to shareholders. This analysis provides important insights into the company's financial health and performance as well as areas that require improvement to ensure sustainability and continued growth.